Florence as “Paradise Lost” - Crum, Roger J. 1962- (2018)
The city of Florence has been a place of artistic pilgrimage for centuries. This essay discusses late nineteenth- and early twentieth-century British and American interest in Florence and, specifically, two of its masterpieces in Ghiberti’s Gates of Paradise and Botticelli’s Birth of Venus as indicative of a melancholic perspective on the Florentine Renaissance as a “Paradise Lost.” The city was ambivalently idealized as an “Earthly Paradise.”
Keywords: Florence -- Dante -- Domenico Michelino -- Renaissance -- Grand Tour -- tourism -- Lorenzo Ghiberti -- Sandro Botticelli -- Walter Pater -- Bernard Berenson -- Chalres Eliot Norton -- E.M. Forster -- Venus -- Pluto and Proserpina -- Jeff Koons